COBIT 2019 Framework: Evaluating Knowledge and Quality Management Capabilities in a Printing Machine Distributor - Beato, Jonathan; Fianty, Melissa Indah (Universitas Bina Darma, 2024)
Within the realm of printing machine distribution, information technology assumes a critical role in streamlining business operations. This study addresses persistent challenges related to inaccurate inventory data and insufficient knowledge management in IT applications. Utilizing the COBIT 2019 framework to assess IT governance capability, qualitative data was collected through interviews to uncover prevailing issues. The findings underscore specific process objectives—APO11 (Managed Quality), BAI08 (Managed Knowledge), and DSS06 (Managed Business Process Controls)—highlighting the need for improved capability levels. For example, APO11 currently resides at level 3 while aiming for level 4, indicating a one-level discrepancy. Similarly, BAI08 and DSS06 are at level 2, signaling a collective two-level gap. Proposed enhancements center on bolstering IT knowledge management and procedural training to meet quality standards in future IT applications. These measures aim to strengthen organizations, aligning IT practices with business processes to ensure heightened quality and efficiency. Notably, this abstract intentionally omits explicit mention of the evaluated IT process, adhering to the specified guideline.